2023
DOI: 10.3390/nu15061390
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Dose-Response Meta-Analysis on the Relationship between Different Gluten Doses and Risk of Coeliac Disease Relapse

Abstract: Gluten proteins are known as immunological triggers for inflammation resulting in mucosal lesions in patients with coeliac disease (CD). Adherence to a strict gluten-free diet (GFD) is currently known as the only effective treatment for CD. In this study, we performed a systematic review and dose-response meta-analysis on data from previous studies to investigate the association between different gluten doses administered and the risk of CD relapse. Electronic databases were systematically searched to retrieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 46 publications
(58 reference statements)
0
5
0
Order By: Relevance
“…This form of network visualization led to the comprehension of connections between metabolites and studies. Next, bipartite network projection that is extensively used for compacting data about bipartite networks was obtained 23–25 . Network projection was employed to streamline bipartite networks by converting them into unipartite networks.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This form of network visualization led to the comprehension of connections between metabolites and studies. Next, bipartite network projection that is extensively used for compacting data about bipartite networks was obtained 23–25 . Network projection was employed to streamline bipartite networks by converting them into unipartite networks.…”
Section: Methodsmentioning
confidence: 99%
“…Next, bipartite network projection that is extensively used for compacting data about bipartite networks was obtained. 23 , 24 , 25 Network projection was employed to streamline bipartite networks by converting them into unipartite networks. This conversion aided in the more efficient analysis of the relationships within the data.…”
Section: Methodsmentioning
confidence: 99%
“…Rostami-Nejad et al [47] carried out a systematic review and meta-analysis in Iran and found that an intake of 6 ppm/day of gluten was accompanied by a 0.2% chance of CD recurrence, which increased to 1.8% with the consumption of 40 ppm/day of gluten, reaching 50% at the amount of 881 ppm and 100% at the amount of 1500 ppm of gluten per day. The duration of gluten ingestion also showed a positive relationship with CD recurrence, showing that exposure time is as important as quantity.…”
Section: Cross-contamination In Gluten-free Productsmentioning
confidence: 99%
“…Indeed, a study that analysed the gluten contamination of oats used in 12 important clinical studies showed how this contamination was related to the presence of symptoms in study patients, even if the estimated amount of gluten in the products did not seem to have an impact on the morphological outcome in treated patients [68]. Studies indicate a dose-dependent association between gluten intake and CD-relapse risk, ranging from 0.2% with 6 mg/day to 100% with 1.5 g/day of gluten [69]. However, to date, there are no consistent data that allow us to specifically quantify the impact that gluten contamination has on the course of a patient's disease.…”
Section: Gluten Contaminationsmentioning
confidence: 99%